Stock market participation, work from home, and inequality - Lorenz Meister; Lukas Menkhoff; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Stock market participation among working household heads jumped upwards in 2020 - in Germany by about 25%. A major cause is the required use of work from home (WfH). We show this by adding WfH to a large set of explanatory variables. Moreover, we implement an instrumental variables estimation based on industry-specific levels of WfH-capacity. The transmission channels seem to work via increased available time and time flexibility. Moreover, we show that WfH makes the stock market accessible to a broader population, including lower income groups, which may contribute to lower income inequality in the future.
Keywords: D31; G11; G51; 330; stock market participation; work from home; inequality